La formación de armadas y sus efectos sobre el territorio: el ejemplo de Galicia, 1580-1640 - Saavedra Vázquez, María Del Carmen (Cuadernos de Historia Moderna, 2006)
This article deals with the involvement of Galicia in the naval activity of the Hapsburgs from the late sixteenth century to the fourth decade of the seventeenth century. A review is first made of the nature and substance of Galician contributions to royal navies; a second section then looks at the efforts made in the region to set up and maintain its own fleets. The following sections then discuss the repercussions of both initiatives, with a general estimate of their effects on the territory, finally homing in on the situation of a specific navy. Taking as reference the stay of the royal navy in A Coruña in the winter of 1608, a detailed analysis is made of the type and value of the area’s victualling contributions and the identity of the suppliers and workers. This gives an approximate idea of the social distribution of its impact and also a preliminary picture of the main beneficiaries of the navy’s presence.